Long-term treatment with alendronate increases the surgical difficulty during simple exodontias - an in vivo observation in Holtzman rats - Conte-Neto, Nicolau [UNESP]; Bastos, Alliny de Souza [UNESP]; Spolidório, Luis Carlos [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Marcantonio, Elcio [UNESP] (Biomed Central Ltd., 2012)
Background: Atraumatic teeth extractions protocols are highly encouraged in patients taking bisphosphonates (Bps) to reduce surgical trauma and, consequently, the risk of jaws osteonecrosis development. In this way, this paper aims to report the findings of increased surgical difficulty during simple exodontias in animals treated with bisphosphonates.Methods: Sixty male Holtzman rats were randomly distributed into three groups of 20 animals and received daily subcutaneous administration of 1 mg/kg (AL1) or 3 mg/kg (AL3) of alendronate or saline solution (CTL). After 60 days of drug therapy all animals were submitted to first lower molars extractions under general anesthesia. Operatory surgical time and the frequency of teeth fractures were measured as principal outcomes and indicators of surgical difficulty degree.Results: Animals treated with alendronate (AL1 and AL3) were associated to higher operatory times and increased frequency of teeth fractures compared to match controls.Conclusions: The bisphosphonate therapy may be associated with an increased surgical difficulty and trauma following simple exodontias protocols, which is considered a critical issue when it comes to osteonecrosis development.
Keywords: Bisphosphonates; Tooth extraction; Osteonecrosis